2016
DOI: 10.1111/trf.13654
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with or without plasma exchange for patients with acquired thrombotic microangiopathy not associated with severe ADAMTS13 deficiency: a propensity score–matched study

Abstract: Our data suggest that routine use of TPE in the diverse group of TMA patients without severe ADAMTS13 deficiency may not significantly improve outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 33 publications
6
30
0
1
Order By: Relevance
“…However, recent evidence has shown that when TMA occurs as the result of a systemic illness, the ADAMTS13 activity is typically normal or mildly deficient, and patients do not respond to PEX. 2 In these cases, the treatment should be directed toward treating the underlying disease or stopping the offending drug. In the following review, we will discuss specific etiologies of TMA that should be considered after acquired TTP has been ruled out by nondeficient ADAMTS13 activity (.10%) and alternatives to a diagnosis of aHUS are being considered (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent evidence has shown that when TMA occurs as the result of a systemic illness, the ADAMTS13 activity is typically normal or mildly deficient, and patients do not respond to PEX. 2 In these cases, the treatment should be directed toward treating the underlying disease or stopping the offending drug. In the following review, we will discuss specific etiologies of TMA that should be considered after acquired TTP has been ruled out by nondeficient ADAMTS13 activity (.10%) and alternatives to a diagnosis of aHUS are being considered (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the literature, the turnaround time for this test from a reference laboratory is approximately 3 days . After 3 days, using the result of the ADAMTS13 assay, the subsequent management for this scenario is assumed to be identical to the scenarios involving the in‐house ADAMTS13 testing (i.e., the only difference is the 3‐day TPE). An in‐hospital ADAMTS13 analysis with TPE initiated only if the ADAMTS13 is less than 10% (i.e., confirmed TTP): When positive (for both true‐ and false‐positive cases), the patient undergoes TPE for 3 days, resulting in the same pathways as Scenario 1 with appropriate mortality rate adjustment for true‐ and false‐positive cases (Table ) . In cases when the patient's test result is negative (i.e., ADAMTS13 is ≥ 10%), TPE is not performed as TTP has been excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, therapeutic plasma exchange (TPE) is indicated for acquired TTP, which reduces the mortality rate to 10% to 30% . However, TPE has little efficacy in treating other forms of TMAs . For example, eculizumab, an anticomplement therapy, is the treatment of choice for atypical hemolytic uremic syndrome .…”
mentioning
confidence: 99%
“…The second test, which was based on an assumption of common support, required the p-score density function of the two groups to be proximate, indicating similar characteristics of X in both groups after matching. Simultaneous satisfaction of the balancing hypothesis and the common support assumption would demonstrate that the farm households did in fact behave similarly [21].…”
Section: The Propensity Score Matching Proceduresmentioning
confidence: 99%